2022
DOI: 10.21272/mmi.2022.4-07
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Transport Infrastructure of Global Logistics: Cross-Country Analysis

Abstract: In modern society, there is a constant development and improvement of the transport industry, due to which the role and distribution of this logistics industry, which is a service, is growing for the high-quality and fast delivery of goods. To maximize the export of finished products and more effective penetration into international markets around the world are organized by global logistics systems. This article summarizes the arguments and counterarguments within the scientific discussion on the place and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Three main factors can be identified that have affected logistics-related business processes (Abesadze, 2022;Rahmanov, 2022;Hrashchenko, 2020):…”
mentioning
confidence: 99%
“…Three main factors can be identified that have affected logistics-related business processes (Abesadze, 2022;Rahmanov, 2022;Hrashchenko, 2020):…”
mentioning
confidence: 99%